Clinical management and therapeutic outcome of infertile couples in southeast Nigeria - Menuba, Ifeanyi E (Dove Medical Press, 2014)
BACKGROUND: Infertility is highly prevalent in Nigeria and most infertile couples in southeast Nigeria are offered conventional forms of treatment, which consist mainly of ovulation induction and tubal surgery, due to limited availability and high cost of endoscopic and assisted reproductive technologies like laparoscopy and in vitro fertilization. The aim of this study was to determine the prevalence of infertility, outcome of infertility investigation, and the treatment outcome of infertile couples following therapeutic interventions in southeast Nigeria over a 12-month period. METHODS: This was a prospective cross-sectional study of 218 consecutive infertile couples presenting for infertility management at the infertility clinics of two tertiary health institutions in Enugu, southeast Nigeria. Infertility investigations were carried out on these couples using the available conventional diagnostic facilities. Following the results of the investigations/diagnosis, conventional treatment was offered to the couples as appropriate. Data analysis was both descriptive and inferential at 95% confidence level. RESULTS: The mean age of the women was 33.5±4.62 (range: 15–49) years. Most (58.3% [n=127]) were nulliparous. The prevalence of infertility was 12.1%. Infertility was primary in 28.4% (n=62) and secondary in 71.6% (n=156). Female etiologic factors were responsible in 32.1% (n=70), male factors in 26.1% (n=57), and a combination of male/female factors in 29.4% (n=64). The etiology was unknown in 12.4% (n=27). Tubal factors 23.8 % (n=52) and ovulation failures 26.1% (n=57) are common female factors implicated. Pregnancy rate following treatment was 16.7% (n=28). Multivariate regression analysis indicates that younger age of ≤30 years, duration of infertility ≤5 years, and female factor infertility were associated with higher pregnancy outcome following treatment. CONCLUSION: The prevalence of infertility is high and pregnancy rate following conventional treatment is poor. There is a need to improve facilities for managing infertility as well as making artificial reproductive techniques readily available, accessible, and affordable.